Degradation of Fusobacterium nucleatum biofilm and quantity of reactive oxygen species due to a combination of photodynamic therapy and 2.5% sodium hypochlorite - Nanik Zubaidah; Sukaton; Sri Kunarti; Meidi Kurnia Ariani; Dawailatur Rahman Setiady; Dur Muhammad Lashari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: The persistence of microorganisms in the root canal system is one of the leading causes of root canal treatment failure. Biofilms of putative pathogens hidden inside dentin tubules and other root canal ramifications may limit current disinfection protocols. Photodynamic therapy (PDT) with a wavelength of 628 nm can be used as an antimicrobial strategy that uses low-power laser energy to activate a non-toxic photosensitizer to produce singlet oxygen with the ability to kill microorganisms in root canals. Fusobacterium nucleatum was used because this bacterium is one of the bacteria involved in root canal infection. Purpose: The aim of this study was to compare the bactericidal efficacy of sodium hypochlorite (NaOCl) 2.5%, PDT, and a combination of PDT and NaOCl 2.5% against Fusobacterium nucleatum. Methods: Mature biofilm Fusobacterium nucleatum was divided into four groups according to the protocol of decontamination: K1 (negative control – biofilm), K2 (NaOCl 2.5%), K3 (PDT), and K4 (NaOCl 2.5% + PDT). Biofilm degradation was observed using optical density (OD) at 570 nm using a microplate reader. A reactive oxygen species quantity check was carried out using a nitroblue tetrazolium test, and OD observation was done with a microplate reader at 540 nm. Results: Group 4 (NaOCl 2.5% + PDT) showed more biofilm bacteria elimination than the other groups. Conclusion: A combination of PDT and NaOCl 2.5% can be considered an effective protocol for the elimination of Fusobacterium nucleatum. There is a potentiation relationship between NaOCl 2.5% and PDT FotoSan. Biofilm degradation occurs because of the effect of antibacterial NaOCl 2.5% and the irradiation effect of the Toluidine blue O photosensitizer.